FACTORS INFLUENCING THE DECISION OF CONVENTIONAL/HYBRID LIGHTWEIGHT DESIGN STRATEGIES AND THEIR EFFECT ON THE DESIGN PROCESS. (May 2020) - Schmitt, P.; Gericke, K.
Abstract: Lightweight design (LWD) is partly reaching its limits. New technologies must not only be used to make products more functional, but also to make LWD more efficient. Here additive manufacturing (AM) should be named. Potentials of the use in LWD are not yet clear. In this work, existing LWD strategies and their location in the design process are presented. Criteria are worked out which influence the design process and the use of LWD strategies. The use of AM in (hybrid) LWD will be investigated in order to overcome design trade-offs and what influence its use could have on the design process.